Gerakan Bersih Pantai sebagai upaya Mengurangi Sampah Dikawasan Pantai Nambo, Kota Kendari, Sulawesi Tenggara, Indonesia - Siti Rabbani Karimuna; Azyuyun Azyuyun; Aliyyah Nisrina Taufik; Fitra Sawfla Insani; Nilda Fadila; Bulan Sari; Aurel Amelia Putri Taoha; Selvi Safitri; Indri Reva Wardani; Asnita Sari; Nur Yanti; Wiwid Arsanda; Ihsan Adi Sasono (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
Coastal environmental pollution, especially due to plastic waste, has become a serious threat to marine ecosystems and public health. Nambo Beach in Kendari City, Southeast Sulawesi, is one of the areas affected by the lack of waste management and low public awareness. This community service activity aims to increase community awareness and participation in maintaining beach cleanliness through clean-up actions and environmental education. The methods used include collecting rubbish by students and providing education to visitors through poster media. The results of the activity show that there is community enthusiasm for this activity as well as increased understanding of the importance of protecting the environment. Visual education has proven effective in conveying environmental messages, while beach clean-up actions encourage direct behavior change. This activity proves that collaboration between academics and the community can create a positive impact and needs to be implemented sustainably as part of a participatory-based waste management strategy in coastal areas.